Civil Disabilities : Citizenship, Membership, and Belonging - Hirschmann, Nancy J.; Linker, Beth (Book collections on Project MUSE., 2015)
Urges a reconceptualization of disability and citizenship to secure a rightful place for disabled persons in society. Essays from leading scholars in a diversity of fields offer critical perspectives on current citizenship studies, which still largely assume an ableist world. Placing historians in conversation with anthropologists, sociologists with literary critics, and musicologists with political scientists, this interdisciplinary volume presents a compelling case for reimagining citizenship that is more consistent, inclusive, and just, in both theory and practice. By placing disability front and center in academic and civic discourse, Civil Disabilities tests the very notion of citizenship and transforms our understanding of disability and belonging.